Association Between Dietary Inflammatory Index and S-Klotho Plasma Levels in Middle-Aged and Elderly People - Ma, Teng-Chi; Zhou, Jing; Wang, Chen-Xi; Fang, Min; Gao, Feng (Frontiers in Nutrition, 2022)
Background and Aims Soluble Klotho (S-Klotho) is a protein that has anti-aging properties. Dietary inflammation index (DII) is closely related to various age-related diseases. However, whether DII is related to S-Klotho plasma levels is still controversial. It was the goal of this study to examine the link between DII and S-Klotho in middle-aged and elderly people. Methods Between 2007 and 2016, five NHANES cycles were conducted, with 12,315 middle-aged and elderly (aged 40–79) participants having S-Klotho tests and submitting dietary recall data. The inflammatory potential of a diet was determined using the DII. To determine the plasma levels of S-Klotho, we employed a solid-phase sandwich enzyme-linked immunosorbent assay (ELISA). Results There was a negative correlation between DII and S-Klotho plasma levels. In the threshold effect analysis model, the breakpoint was DII=1.3, and the negative correlation was more obvious when DII < 1.3 (β = −10.6, p = 0.001). When DII > 1.3, the correlation disappeared (p = 0.355). There may be a threshold saturation effect. Conclusion In middle-aged and older individuals, there is a negative connection between the pro-inflammatory dietary pattern as evaluated by DII and the plasma level of S-Klotho. Given the rationale for the findings and the study's limitations, the fundamental mechanisms generating inflammation warrant additional exploration.